GaN tubes with coaxial non‐ and semipolar GaInN quantum wells. Issue 3 (17th February 2014) - Heinz, Dominik; Fikry, Mohamed; Aschenbrenner, Timo; Schowalter, Marco; Meisch, Tobias; Madel, Manfred; Huber, Florian; Hocker, Matthias; Frey, Manuel; Tischer, Ingo; Neuschl, Benjamin; Mehrtens, Thorsten; et al.
Abstract: We present the position‐controlled growth of GaN nanotubes with coaxial GaInN quantum wells by using ZnO nanowires grown on top of GaN pyramids as templates. High resolution scanning transmission electron microscopy allows us to perform a detailed structural analysis of individual tubes. In particular, we report about structural properties like indium incorporation, thickness, and homogeneity of quantum wells realized on nonpolar m‐plane side facets or on semipolar tips. Additionally, high resolution spatially and spectrally resolved cathodoluminescence spectroscopy performed at low temperature enables us to clearly identify the quantum well luminescence contributions for different kinds of facets on a single tube. The luminescence of the quantum wells deposited at variable temperatures shows a clear spectral shift in the cathodoluminescence signal, yielding an activation energy for the indium desorption from the m‐plane side facets of about 1.6 eV. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)